2022
DOI: 10.1002/tbio.202200016
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology and photodynamic therapy from a clinical perspective

Abstract: Photodynamic therapy (PDT) is currently applied clinically in many medical centers worldwide. The clinical outcomes are from one side satisfying and from the other side highlighting the areas of further development. Issues like hydrophobicity of the photosensitizer (PS), uncontrolled distribution and limited tissue penetration of the accompanying light sources triggered the interest of many research groups. Nanotechnology outstood among the various suggested enhancement solutions. In this review, the rationale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…A dual-mode polymeric nanosystem was developed where the core was loaded with the chemotherapeutic agent oxaliplatin and the shell contained a pyropheophorbide derivative as a photosensitizer. Photodynamic therapy is a local therapeutic approach that relies on the combination of a photosensitizer, light source, and cellular oxygen and is commonly combined with nanotechnology for response enhancement. , Upon illumination, oxaliplatin release was triggered, reactive oxygen species (ROS) were generated, and the resultant synergistic chemophotodynamic therapy suppressed tumor growth and metastasis. Coadministration with immunotherapy using antibodies against programmed death-ligand 1 (PD-L1) resulted in the recruitment of CD8 + and CD4 + T cells .…”
Section: Polymer-based Nps As Cancer Vaccine Platformsmentioning
confidence: 99%
“…A dual-mode polymeric nanosystem was developed where the core was loaded with the chemotherapeutic agent oxaliplatin and the shell contained a pyropheophorbide derivative as a photosensitizer. Photodynamic therapy is a local therapeutic approach that relies on the combination of a photosensitizer, light source, and cellular oxygen and is commonly combined with nanotechnology for response enhancement. , Upon illumination, oxaliplatin release was triggered, reactive oxygen species (ROS) were generated, and the resultant synergistic chemophotodynamic therapy suppressed tumor growth and metastasis. Coadministration with immunotherapy using antibodies against programmed death-ligand 1 (PD-L1) resulted in the recruitment of CD8 + and CD4 + T cells .…”
Section: Polymer-based Nps As Cancer Vaccine Platformsmentioning
confidence: 99%
“…However, their low hydrophilicity limits their bioavailability. Several solutions were proposed to overcome this limitation, and utilizing nanoparticles was one of the successful strategies that showed promising results at the clinical level [ 63 ]. A full spectrum of nanoparticles including metallic, polymeric, carbon-based, and nanosheets combined with PDT for skin, bone, and cartilage healing was presented in an earlier review [ 64 ] Throughout the four identified wound healing stages, nanoparticles such as ceramics, lipids, nanohydrogels, and nanocomposites, in addition to other forms loaded with PSs, showed a significant improvement in the wound healing outcome, as summarized earlier [ 65 ].…”
Section: Major Limitations Of Pdtmentioning
confidence: 99%
“…In conclusion, PDT can be a promising candidate to enhance the efficacy of various other therapeutic modalities and serve as an ideal adjuvant treatment. Nevertheless, the appropriate use of combinations like immunotherapy, chemotherapy, and biological treatments following PDT/PDP has been reported to enhance therapeutic outcomes [7,64,73,74]. Therefore, this represents a very promising approach for achieving optimal survival outcomes.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%